EFEKTIVITAS PERJANJIAN BAGI HASIL TANAH GARAPAN DI WILAYAH PEDESAAN NTB: KAJIAN YURIDIS DAN SOSIOLOGIS - Hilman Prayuda (Universitas Harapan Medan, 2025)
This study evaluates the practice of sharecropping agreements between tenant farmers and landowners in rural areas of West Nusa Tenggara (NTB), which are generally conducted orally based on longstanding traditions and local values. These agreements are often made informally without written documentation, relying primarily on trust and established social relationships between the parties. The main objective of this research is to assess the effectiveness and legal validity of oral sharecropping agreements within the framework of national civil law, while also considering the dynamics of customary law (adat) as it operates in local communities. Employing a juridical-empirical approach, this study examines relevant legal instruments, including the Indonesian Civil Code (KUHPerdata) and Law No. 2 of 1960 concerning Sharecropping Agreements, alongside field data obtained through interviews and direct observation in the villages of Puyung and Ketare (Central Lombok) and Suralaga (East Lombok). The findings indicate that oral sharecropping agreements are legally valid under Article 1320 of the Civil Code, provided they meet the essential elements of consent, legal capacity, a specific object, and a lawful cause. However, such agreements are significantly weak in terms of evidentiary value in dispute resolution and fail to provide sufficient legal protection for farmers, who are typically the more vulnerable party socially and economically. This imbalance creates inequality in the legal relationship between farmers and landowners. Therefore, the study recommends the implementation of simple formalization measures through local registration or village records, and the strengthening of customary legal institutions via village-based regulations, to ensure legal certainty and substantive justice for all parties involved in agrarian agreements.